Calculation the thermodynamic parameters required for stability of roton - Ismail, Nasser (Latakia University Journal -Basic Sciences Series, 2019)
This work aims to search about the thermodynamic properties of phonons and rotons in Hellium II (thermodynamic potential, roton energy, particles number). It is noticed from the curves the energy gap depth in roton cell has a value of Correspond to wave number . In addition, the curve of the ratio between normal component density ρn to the total density of liquid helium ρ as a function of temperature. The diagram illustrated the difference between in the range (0.9 – 1.8)K.